Study of physicochemical properties and sorption capacity of developed composite sorbents KHR-OKS for use in the process of cyanidation and sorption (Международный научный журнал «Инженер», 2026)
Currently, the basic matrix structures for chemical modification and production of ion exchangers are styreneand acrylic copolymers cross-linked with divinylbenzene. By adjusting the copolymerization conditions, it ispossible to obtain not only a given size, but also other parameters of the initial polymer granules important forthe synthesis of ion exchangers, primarily porosity. Copolymers of styrene with divinylbenzene are a universalmatrix for obtaining both main classes of ion exchangers - cation exchangers and anion exchangers. In thisregard, the search for new ion exchangers with a set of valuable indicators is of great practical interest. Therefore,recent research in the field of creating competitive products is aimed at effective methods for modifying existingion exchangers in order to impart to them improved indicators of such basic properties as increased thermal andchemical resistance, fairly good indicators of kinetic, sorption, and selective characteristics. This, in turn, issolved by using a modern approach to obtaining products and issues of rational use of available initial resourcesand secondary products of production.